Antiepileptic drug exposure in pregnancy and pregnancy outcome from national drug usage data - Richards, Noni (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Antiepileptic drugs (AEDs) are used by pregnant women to manage conditions such as epilepsy and bipolar disorder even though they pose a risk to the developing foetus. This study aimed to determine the overall use of AEDs by women during their childbearing years and women who are pregnant and the association between AED use and rates of pregnancy termination and spontaneous abortion. METHODS: Retrospective population based cohort study using administrative databases in New Zealand between 2008 and 2014. Women who had been pregnant were identified by the National Minimum Dataset and were linked to the Pharmaceutical Collection to obtain information on use of AEDs. Women aged between 15 and 45 years dispensed AEDs were identified in the Pharmaceutical Collection. RESULTS: There was an increase in the number of women of child-bearing potential prescribed AEDs, from 9 women per 1000 women in 2008 to 11.4 women per 1000 women in 2014. Women who had been dispensed an AED had an increased rate of spontaneous abortion 8.97 spontaneous abortions per 100 pregnancies, compared with, 6.31 per 100 pregnancies (risk ratio 1.42, 95% CI 1.40 to 1.44), and a decreased rate of pregnancy termination, 18.51 terminations per 100 pregnancies compared with 19.58 per 100 pregnancies (risk ratio 1.95, 95% CI 0.94–0.96). CONCLUSION: Use of newer AEDs is increasing in women of child-bearing potential in New Zealand leading to an overall increase in AED use in this group despite a fall in the use of older AEDs. AED use is this study was associated with an increased risk of spontaneous abortion and decreased rate of pregnancy termination, however confounding by indication could not be excluded.